One-year outcomes of microshunt implantation in pseudoexfoliation glaucoma. - Matthias Nobl (Public Library of Science (PLoS), 2021)
Purpose To compare the safety and efficacy of microshunt implantation augmented with Mitomycin C in patients with pseudoexfoliation glaucoma (PEXG) and primary open-angle glaucoma (POAG). Methods In this retrospective, single centre, interventional study, 46 eyes of 41 patients with PEXG (20 eyes) and POAG (26 eyes) underwent microshunt implantation. Definition of failure was an intraocular pressure (IOP) lower than 5 or higher than 17mmHg on two consecutive visits, an IOP reduction lower than 20% on two consecutive visits, the need of surgical revisions or reoperations or loss of light perception. Outcome was rated as complete success if achieved without medication, otherwise as qualified success. Furthermore, postoperative complications and interventions were compared between the two groups. Results Patient demographics were similar, except for older age in the PEXG group (70.9±8.6 versus 77.6±8; p = 0.02). Mean IOP dropped from 21.5±5.8mmHg (PEXG) and 18.2±4.5mmHg (POAG) at baseline to 12.8±3.0mmHg (p<0.0001) and 12.9±4.2mmHg (p<0.0001), respectively, at one year. Mean number of medications were reduced from 2.8±1.3 to 0.3±0.8 for PEXG patients (p<0.0001) and from 2.7±1.3 to 0.3±0.8 for POAG patients (p<0.0001). At one year of follow-up 75.0% of PEXG patients achieved complete success and 80.0% qualified success. In the POAG group rates were 73.1% and 76.9%, respectively. Postoperative complications were comparable between both groups, except for higher rates of hypotony (p = 0.04) and choroidal detachment (p = 0.03) in the PEXG group. Conclusion Microshunt implantation demonstrated similar efficacy results in PEXG and POAG eyes at a follow-up of 12 months. Higher rates of transient hypotony and choroidal detachment were observed in PEXG eyes.